2001
DOI: 10.1107/s0108270101003675
|View full text |Cite
|
Sign up to set email alerts
|

Two rhodamine derivatives: 9-[2-(ethoxycarbonyl)phenyl]-3,6-bis(ethylamino)-2,7-dimethylxanthylium chloride monohydrate and 3,6-diamino-9-[2-(methoxycarbonyl)phenyl]xanthylium chloride trihydrate

Abstract: The title compounds, C28H31N2O3(+)-Cl(-)-H2O (common name rhodamine-6g), (I), and C21H17N2O3(+)-Cl(-)-3H2O (common name rhodamine-123), (II), both have planar xanthene skeletons with a formal +1 charge on the amino N atoms delocalized through the pi-electron system so that the N-Csp(2) bond distances indicate significant double-bond character. The substituted planar phenyl groups make angles of 63.29 (8) and 87.96 (11) degrees with the xanthene planes in (I) and (II), respectively. In both molecules, the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 7 publications
1
20
3
Order By: Relevance
“…Total 48 and 38 rotation series for the rt and cryo datasets, respectively (numbers of datasets are written in the same manner below), were first ×2 binned, and processed with DIALS for indexing and integrating of diffraction spots. We found that the crystal form was different from that previously reported 19 . Reduced datasets were grouped and sorted by KAMO 42 , which carried out scaling and merging by using Pointless 43 , XSCALE 44 and BLEND 45 .…”
Section: Electron Crystallographycontrasting
confidence: 96%
See 1 more Smart Citation
“…Total 48 and 38 rotation series for the rt and cryo datasets, respectively (numbers of datasets are written in the same manner below), were first ×2 binned, and processed with DIALS for indexing and integrating of diffraction spots. We found that the crystal form was different from that previously reported 19 . Reduced datasets were grouped and sorted by KAMO 42 , which carried out scaling and merging by using Pointless 43 , XSCALE 44 and BLEND 45 .…”
Section: Electron Crystallographycontrasting
confidence: 96%
“…Extended Data Table 2), but different from the triclinic crystal structure with chlorine determined previously by XRD from a single crystal, in which the planes of the two rings are oblique to each other rather than normal 19 (Extended Data Fig. 2, f-h).…”
Section: Competing Interestscontrasting
confidence: 54%
“…From the crystal data about the Acridine Orange cation (Obendorf et al 1976;Reddy et al 1979;Mattia et al 1984Mattia et al , 1995Kuban et al 1985;Gordon et al 2003), the Proflavine cation (Jones and Neidle 1975;Shieh et al 1980Shieh et al , 1982Swaminathan et al 1982;Aggarwal et al 1984;Ara and El Bahij 2004;Varga et al 2007), Methylene Blue (Marr et al 1973;Kahn-Harari et al 1973;Endres et al 1977;Snaathorst et al 1981;Enescu et al 2000;Sours et al 2002;Kavitha et al 2004;Li et al 2005;Soneta and Miyamura 2006;Raj et al 2007), Eosin (Harrison et al 2007), Rhodamine B (Fujii et al 1995;Nishikiori and Fujii 1997;Soneta et al 2006), Ethyl Rhodamine G (Wang et al 1997;Fun et al 1997;Liu et al 1998;Adhikesavalu et al 2001;Zhang et al 2001), Para-rosaniline (Koh and Eriks 1971;Liu et al 2002;Xie 2008), and Crystal Violet (Spangler et al 1989;Lovell et al 1999;Lacour et al 2002;Soneta et al 2006), as well as the substituted 1-phenyl-azo-2-naph...…”
Section: Dye Aggregatesmentioning
confidence: 97%
“…[8] consisting of Rh6G Á HCl Á H 2 O (names: 9-(2-carboxylatophenyl)-3,6-bis-(ethylamino)-2,7-dimethylxanthylium inner salt monohydrate, rhodamine 19 zwitterion, etc.) [7]. For the first time this possible photodegradation process is reported.…”
Section: Resultsmentioning
confidence: 92%